2021
DOI: 10.1002/clc.23584
|View full text |Cite
|
Sign up to set email alerts
|

Discordance between lactic acidemia and hemodynamics in patients with advanced heart failure

Abstract: Background Elevated lactic acid (LA) levels carry a poor prognosis in patients with shock. Data are lacking on the significance of LA levels in patients with acute decompensated heart failure (ADHF). Hypothesis This study assessed the relationship between LA levels, hemodynamics and clinical outcomes. Methods This was a retrospective analysis of registry data of 100 advanced heart failure patients presenting for right heart catheterization (RHC) for concern of ADHF. LA levels (normal ≤2.1 mmol/L) were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Patients with AHF are unable to provide appropriate oxygenation and perfusion of tissues and organs owing to infection, decreased cardiac function, coronary artery stenosis, and other factors, increasing in anaerobic glycolysis and lactic acid build-up [ 19 ]. Narang et al revealed that cardiac index decreases when lactic acid levels rise in individuals with acute decompensated heart failure [ 7 ]. Li et al found that as lactic acid levels climbed, in-hospital mortality in patients with heart failure increased proportionately [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with AHF are unable to provide appropriate oxygenation and perfusion of tissues and organs owing to infection, decreased cardiac function, coronary artery stenosis, and other factors, increasing in anaerobic glycolysis and lactic acid build-up [ 19 ]. Narang et al revealed that cardiac index decreases when lactic acid levels rise in individuals with acute decompensated heart failure [ 7 ]. Li et al found that as lactic acid levels climbed, in-hospital mortality in patients with heart failure increased proportionately [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research by Robert et al has shown that elevated blood lactic acid on admission is common in AHF patients and is associated with markers of a worse prognosis [ 6 ]. Some studies also suggest that lactic acid can predict the prognosis of patients with AHF [ 7 9 ]. The association between the levels of lactic acid and nosocomial all-cause mortality in patients with AHF, especially in the critical care unit, has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%